POLICY EVALUATION OF INDEPENDENT CAMPUS : ANALYSIS STUDY ON THE TEACHING CAMPUS PROGRAM - Abdul Rahman; Winda Dwi Astuti Zebua; Zahriatul Aini; Fahdiansyah Putra (Prodi Ilmu Pemerintahan, Universitas AMIKOM Yogyakarta, 2025)
This research aims to evaluate the Teaching Campus program in 3 evaluation scopes: registration and selection, implementation, and impact. This research was conducted using quantitative descriptive methods. Meanwhile the data used is primary data consisting of statistical data on the results of student selection and participation, the data of budget absorption of the program, and the data from the survey results from: higher education students, heads of schools, and fields assistant lecturers. Meanwhile, data analysis was carried out using a responsive evaluation model. This research concludes that the policy evaluation of Independent Campus on the Teaching Campus program is generally quite good, but there are still aspects that need to be improved/optimized such as: Less competitive number of applicants due to ratio of applicants to recipients is only 2 :1, big gap in composition of student registrants from academic higher education levels to vocational higher education levels with a ratio of 2.47%: 97.53%, program implementation tends to be concentrated in the Western Part of Indonesia, and credit recognition is not yet optimal since there are still 22.82% of students who get less recognition of 20 credits.